2002
DOI: 10.1080/00034980120103478
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of personal education plans in continuing professional development: an evaluation

Abstract: A general approach to curriculum design in the context of Problem-Based Learning (PBL) is outlined. Ten general 'steps' for problem-based curriculum development are proposed, using the case study methodology to describe the underlying iterative process. Examples are given from the case of the development of a public health professions education curriculum. The process starts with defining the purpose of the curriculum. General objectives are generated in a top-down fashion. The prior knowledge, skills and misc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Empirical evidence on the impact or effectiveness of PDPs is limited (e.g., Austin et al 2005;Evans et al 2002;Zeichner and Wray 2001). As a consequence, the implementation of the tool by human resource management (HRM) is accompanied by different assumptions and hypotheses.…”
Section: The Goal Of This Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence on the impact or effectiveness of PDPs is limited (e.g., Austin et al 2005;Evans et al 2002;Zeichner and Wray 2001). As a consequence, the implementation of the tool by human resource management (HRM) is accompanied by different assumptions and hypotheses.…”
Section: The Goal Of This Literature Reviewmentioning
confidence: 99%
“…(Continuing) professional development is defined as: "the systematic maintenance, improvement, and broadening of knowledge and skills and the development of personal qualities necessary for the execution of professional and technical duties throughout the practitioner's working life" (Friedman and Philips 2004). Within the context of medicine, it can be defined as "a process of lifelong learning for all individuals and teams which enables professionals to expand and fulfill their potential, and which also meets the needs of patients and delivers the health care priorities of the NHS" (Department of Health 1998, p. 6, in Evans et al 2002). Evans et al (2002) researched the use of PDPs to stimulate the continuing professional development of general practitioners (GPs).…”
Section: Effectivenessmentioning
confidence: 99%
“…To structure and support the actual use of feedback, an often used tool is the Personal Development Plan (PDP) or Personal Learning Plan (Challis 2000;Evans et al 2002). PDPs are generally part of a portfolio, an accepted method to stimulate self refection in performance assessment (Carraccio & Englander 2004;Tochel et al 2009).…”
Section: Practice Pointsmentioning
confidence: 99%
“…More specifically, the Beausaert et al review study (2011) on the effectiveness of PDPs as assessment tools (a total of 54 studies were included in the review) showed that in most empirical studies PDPs are found to be effective for personal or continuing professional development purposes, for stimulating reflection and for improving the professional practice or performance. For example, Evans et al (2002), by taking questionnaires, analyzing PDPs and indepth interviews, studied the use of PDPs to stimulate the continuing professional development of General Practitioners (GPs). They concluded that PDPs are effective tools to stimulate the continuing professional development and personal development of GPs, on the basis that it leads to changes in patient care.…”
Section: Purposes Of a Pdp?mentioning
confidence: 99%
“…For example, a survey in the Netherlands among companies in the region of Limburg indicated that in the context of talent management 89% of the companies are using PDPs (GITP 2008). In the UK, different authors stress the strong recommendation by the government to use PDPs in order to stimulate the continuous professional development of health service (Evans et al 2002;Bullock et al 2007).…”
Section: Introductionmentioning
confidence: 99%